2022
DOI: 10.5935/1984-0063.20220075
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic decreased sleep quality of medical students

Abstract: Objective: Medical students are especially vulnerable to situations of poor sleep quality due to academic demands. The COVID-19 pandemic brought significant changes and high psychological stress, causing a great impact on this population. Here we aim to analyze the influence of the pandemic on the sleep quality of medical students. Methods: Cross-sectional, observational, and descriptive study with a quantitative approach carried out with students from medical universities in Rio Grande do Norte state (Brazil)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is known that sleep quality is a crucial aspect of health and well-being, and its importance has been increasingly discussed in scientific literature. The worrying finding made is corroborated by specific research, such as that carried out with undergraduate nursing students, where more than 80% of participants were classified as having poor sleep quality, as Oliveira 2020 (24) demonstrates that a significant proportion of individuals, around 65.3%, have an inadequate sleep profile, from Silva et al (2020) (25) obtained in students in the fourth period of 73.33% and in the 6th period of 78.26% and as well as the conducted by Fernandes (26) (27,28) .…”
mentioning
confidence: 56%
“…It is known that sleep quality is a crucial aspect of health and well-being, and its importance has been increasingly discussed in scientific literature. The worrying finding made is corroborated by specific research, such as that carried out with undergraduate nursing students, where more than 80% of participants were classified as having poor sleep quality, as Oliveira 2020 (24) demonstrates that a significant proportion of individuals, around 65.3%, have an inadequate sleep profile, from Silva et al (2020) (25) obtained in students in the fourth period of 73.33% and in the 6th period of 78.26% and as well as the conducted by Fernandes (26) (27,28) .…”
mentioning
confidence: 56%
“…The present study and the values found probably had an important impact from the pandemic, but it was not evaluated. One Brazilian study also showed concern about the negative impact of COVID-19 on medical education and the generation of medical jobs, which can also directly worsen sleep quality [40].…”
Section: Discussionmentioning
confidence: 99%
“…All participating students in the study completed the Internet Addiction Test (IAT) to gauge the severity of compulsive internet surfing. The IAT, developed by Young ( 16 ), is widely recognized in international research and has exhibited strong validity and reliability in prior investigations ( 3 , 17 ). The IAT comprises 20 items, each rated on a 5-point Likert scale (1 = rarely, 2 = occasionally, 3 = frequently, 4 = often, and 5 = always).…”
Section: Scales For Questionnairementioning
confidence: 99%